2021
DOI: 10.3390/molecules26061552
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Cytotoxicity Study: Cell Viability and Cell Morphology of Carbon Nanofibrous Scaffold/Hydroxyapatite Nanocomposites

Abstract: Electrospun carbon nanofibers (CNFs), which were modified with hydroxyapatite, were fabricated to be used as a substrate for bone cell proliferation. The CNFs were derived from electrospun polyacrylonitrile (PAN) nanofibers after two steps of heat treatment: stabilization and carbonization. Carbon nanofibrous (CNF)/hydroxyapatite (HA) nanocomposites were prepared by two different methods; one of them being modification during electrospinning (CNF-8HA) and the second method being hydrothermal modification after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…Additionally, the results of immersion into SBF solution revealed that most changes in the Ca/P ratio were found for the HAp70/BG30 sample, indicating the highest bioactivity of all samples. These results agree with previous research [46,47].…”
Section: In Vitro Bioactivity Of the Composite Cementssupporting
confidence: 94%
“…Additionally, the results of immersion into SBF solution revealed that most changes in the Ca/P ratio were found for the HAp70/BG30 sample, indicating the highest bioactivity of all samples. These results agree with previous research [46,47].…”
Section: In Vitro Bioactivity Of the Composite Cementssupporting
confidence: 94%
“…The biocompatibility of nanobers was demonstrated in the literature towards several types of normal cells; recently, mouse broblast exhibited high viability upon treatment with electrospun carbon nanobers modied with hydroxyapatite. 73 Our results indicate the biocompatibility of GNR-containing nanobers, particularly those containing a low concentration of GNR.…”
Section: Development Optimization and Characterization Of The Base Polymeric Nanobersmentioning
confidence: 53%
“…The biocompatibility of nanofibers was demonstrated in the literature towards several types of normal cells; recently, mouse fibroblast exhibited high viability upon treatment with electrospun carbon nanofibers modified with hydroxyapatite. 73 …”
Section: Resultsmentioning
confidence: 99%
“…Electrospun non-woven wound materials have been extensively studied. Because they can be designed to prevent bacterial invasion, promote cell proliferation, as well as adsorption of wound exudates and dehydration of the wound surface 8 , 9 . Furthermore, because of their microporous nature, they can act as the extracellular matrix (ECM) by promoting cell adhesion and migration 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun non-woven wound materials have been extensively studied. Because they can be designed to prevent bacterial invasion, promote cell proliferation, as well as adsorption of wound exudates and dehydration of the wound surface 8,9 . Furthermore, because of their microporous nature, they can act as the extracellular matrix (ECM) by promoting cell adhesion and migration 10,11 .Nanofibers for wound dressing come in a variety of shapes and sizes, they can be prepared from a variety of polymers (natural or synthetic), or they are made by blinding more than one type.…”
mentioning
confidence: 99%